Ekologisk gestaltning - Lidén, Ola (2008)
This paper examines and compares several different sites in Sweden in addition to one in Mexico regarding whether the ecological requirements theses sites have had during planning and construction has affected the design in any way. Is it possible that, for different reasons, one thinks "like nature" when one thinks of ecology and, if true, how does this reflect on the spatial and structural design? This paper tries to identify if some sort of general design expression is used in projects with requirements on ecological sustainability. In total, five projects have been compared in different areas such as choice of materials and their composition.